Rationally designed micropixelation-free tactile sensors via contour profile of triboelectric field propagation. (May 2023) - Seo, Byungseok; Cha, Youngsun; Choi, Yong; Kim, Sangtae; Choi, Wonjoon
Abstract: The explosive increase in demand for portable electronics, including e-skin and touch displays, requires research interest in high-resolution positional tactile sensors. Though in-plane triboelectric field propagation has been recently proposed for tactile sensors achieving good spatial resolution with only a few electrodes, here we present an optimally designed micropixelation-free tactile sensors (mPFTS) to achieve exceptional performances and features in contact and sliding sensing. In the centimeter-scale panel employing only edge electrodes, stimulus positions are accurately sensed by measuring only the voltage ratio between the edge electrodes, with a sensing error of < 7.14%. Additionally, an algorithm involving the signs of the generated voltages accurately senses the sliding motion in terms of the initial contact position, sliding direction, and end position. Numerical modeling and experimental verification of the triboelectric field dynamics reveal the optimization strategies for this tactile sensor. The scalability of the tactile sensor is then demonstrated by constructing an array of panels, proving the potential for industrial applications of the panels. This study will contribute to the further advancement of pixelation-free tactile sensors based on triboelectric field propagation. Graphical Abstract: A micropixelation-free tactile sensor is rationally designed using in-plane triboelectric field propagation that can detect contacting-sliding motions, thereby enabling large-area applications of pixelation-free electric touchpads and panels. ga1 Highlights: A rationally designed micropixelation-free tactile sensor is developed using triboelectric field propagation. Contour profiles of in-plane triboelectric field propagation involve characteristic information of touch detection. Triboelectric voltage ratio between only edge electrodes senses stimulus positions within < 7.14% accuracy. An algorithm involving the signs of the generated voltages enables the precise detection of contacting-sliding motions. The scalability of the tactile sensor is demonstrated by constructing an array of large-area panels.